A Study on the Perception of Selected Ethnic Communities Toward Communication Media : An Empirical Study - Kumar Sharma, Pankaj; Ahmed, Shazeed (Indian Journal of Marketing, 2023)
Purpose : Ethnographic marketing is an emerging area in the field of management. In a world marked by growing multiculturalism, media plays a significant role in the dissemination of information. Marketers are required to know the nature of the perception held by ethnic communities toward media. This is essential to provide tailored media content to respective targeted communities. Hence, the study was carried out to know the perception of ethnic communities toward communication media. Design/Methodology/Approach : The study was conducted using an exploratory research design on a sample of 1,200 units comprising 400 respondents from three ethnic communities selected, namely Bodo, Mishing, and Rabha. The study used a convenience sampling technique, and data were collected by a structured interview schedule. Attitudinal statements were used to record the responses. Multiple discriminant analysis was used for data processing. Findings : The study found that the Rabha community associated media with advertisement as a platform for choice alternatives of products and as an informer of offers. The Bodo community perceived media as the news channel through which information is circulated, but it is not always deemed to be authentic. Finally, the Mishing community perceived media as the educator of people, as the mobilizer of public opinion, and as the provider of information on the latest trends. Practical Implications : As ethnic communities form significant segments of target markets today, the findings are vital inputs for marketers to suitably use the right media for communication in the right perspective. It will consequently facilitate in providing tailored media content to respective communities being targeted by the stakeholders. Originality/Value : Although studies on consumers’ perception toward communication media are available, studies on the specific ethnic communities in the specific geographical region identified are rare. The research findings will go a long way in enlightening academicians as well as marketers who are related to this area and, thus, find it novel. Furthermore, people from the field of anthropology and mass communication may get vital inputs on the behavior of ethnic communities toward media..